Screening commercial disinfectants to strengthen on-farm biosecurity for the prevention of Fusarium wilt of banana Tropical Race 4 in Ecuador - Monserrate-Maggi, Lorena (2026)
Bananas (Musa spp.), often reported together with plantains, are among the most traded fruit commodities worldwide, particularly in terms of export volume and value, with Ecuador recognized as the leading global exporter, supplying approximately one quarter of the total international trade. However, its production is increasingly threatened by climate change and fungal diseases such as Fusarium wilt, caused by Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc TR4). To support preventive management strategies against Foc TR4, this study evaluated the in vitro efficacy of nine commercial disinfectants available in Ecuador—including quaternary ammonium compounds (QACs), oxidizing agents, aldehydes, and alkaline substances—against conidia and chlamydospores of several Foc race 1 strains (VCG0120) as a model organism. Different concentrations and contact times were tested in the presence and absence of organic matter. Chlamydospores exhibited higher resistance than conidia, requiring greater concentrations for inhibition. Aldehyde formulations and QACs achieved the lowest minimum inhibitory concentrations (<1,000 ppm) and remained effective under organic load and variable contact times. These findings emphasize the need to select disinfectants with consistent efficacy under field-relevant conditions to ensure the application of proper biosecurity measures.